2017
DOI: 10.1016/j.rpto.2017.07.004
|View full text |Cite
|
Sign up to set email alerts
|

The Five-Factor model and job performance in low complexity jobs: A quantitative synthesis

Abstract: This article presents the results of four primary studies that investigated the degree to which the Big Five personality dimensions predict job performance in occupations with a low level of job complexity. Job performance was assessed as overall job performance (OJP), task performance (TP), and contextual performance (CP). The results showed that conscientiousness and emotional stability proved to be predictors of the three performance measures. In addition, extroversion was a relevant predictor of OJP and TP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 53 publications
(56 reference statements)
2
17
1
2
Order By: Relevance
“…The total sample size was 43,203 individuals. The oldest study was published in 1933 (Farmer, 1933) and the most recent was published in 2017 (Lado and Alonso, 2017). Therefore, the time period covered by this meta-analysis was 84 years.…”
Section: Methodsmentioning
confidence: 99%
“…The total sample size was 43,203 individuals. The oldest study was published in 1933 (Farmer, 1933) and the most recent was published in 2017 (Lado and Alonso, 2017). Therefore, the time period covered by this meta-analysis was 84 years.…”
Section: Methodsmentioning
confidence: 99%
“…This research has made several unique contributions to the literature on CR. The first unique contribution has been to show that CR is a relevant predictor of job performance and educational outcomes, and that the magnitude of the validity is similar or even more substantial than the validity of other well-studied predictors (e.g., cognitive abilities, personality dimensions; [88][89][90]). Moreover, in the case of academic performance, the findings showed that CR was a valid predictor for the three types of educational outcomes (i.e., GPA, UEM, and EG).…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, it is important that if personality inventories are used for selection purposes, they combine two features: (a) criterion validity and (b) faking resistance. Quasi-ipsative FC personality inventories showed to be the most valid predictors of job performance among all varieties of personality inventories (see, for instance, Lado & Alonso, 2017;Salgado, 2017;Salgado et al, 2015). However, the resistance to faking of quasi-ipsative FC inventories developed for assessing the FFM of personality remained relatively unexplored.…”
Section: Discussionmentioning
confidence: 99%